Hydrophobic Microfiber Strain Sensor Operating Stably in Sweat and Water Environment. Issue 24 (21st October 2018) - Jeong, Sang‐Mi; Kang, Youngsoo; Lim, Taekyung; Ju, Sanghyun
Abstract: Fiber‐based wearable healthcare sensing devices that can monitor the health status of the human body in real time can be affected by sweat from the human body or water from the outside, which may cause the sensor to malfunction. In this study, it is investigated how the fiber strain sensor can operate stably without being affected by sweat or water, even if no additional passivation layer is formed on the outside of fibers applicable to wearable healthcare sensors. The resistance values ​​of the microfiber strain sensor are monitored in real time with the movement of the elbow and knee wraps stitched with a polyurethane (PU)–tin oxide (SnO2 )–carbon nanotube (CNT) composite microfiber. The PU used as a matrix plays a role of naturally increasing or decreasing the fiber according to the movement of the elbow or knee of the body. The CNTs embedded in a PU matrix can monitor the angular movement of the elbow and knee by measuring the changes in electrical resistance. The (1H, 1H, 2H, 2H‐heptadecafluorodec‐1‐yl) phosphonic acid‐coated SnO2 embedded in a PU prevents sweat and water from entering the fiber. This allows to precisely detect elbow and knee movements stably in an external environment exposed to sweat or water. Abstract : A (1H, 1H, 2H, 2H‐heptadecafluorodec‐1‐yl) phosphonic acid‐coated polyurethane–tin oxide–carbon nanotube composite microfiber as a strain sensor, with large stretchability and high stability, can accurately monitor human joint motion suggesting that it can be applicable to detect all minute bending movements in the elbow and knee with a multidimensional angular fabric configuration and predict disease with a healthcare monitoring system.